PENERAPAN TEKNOLOGI BUSINESS INTELLIGENCE DALAM MENINGKATKAN STRATEGI PENJUALAN DENGAN METODE OLAP PADA CAFÉ LE KAHVE - Zendrato, Nur Eni; Sipayung, Arif Richardo Idola; Marbun, Timo Adelina; Telaumbanua, Jeremia Nicholas; Sihombing, Oloan (Politeknik Bisnis Indonesia, 2024)
This research aims to develop a data warehouse system and information dashboard based on Business Intelligence (BI) technology with the OLAP method to improve sales strategies at Le Kahve, a coffee shop company. The BI implementation uses Pentaho Data Integration for the ETL (Extract, Transform, Load) process and Microsoft Power BI for dashboard visualization. The ETL process is carried out to collect, process, and link sales data obtained from the Point of Sales (POS) system in Excel format. The data is then processed into a data warehouse using a star schema, which facilitates multidimensional analysis. Through the OLAP method, sales data is analyzed across various dimensions such as product, time, and payment method. The data visualization results in the form of a dashboard enable the company to quickly view sales performance and make more effective decisions. This dashboard provides information on best-selling products, product categories, and sales trends over time. The research results show that by implementing BI and OLAP, the company can improve operational efficiency, accelerate analysis, and support decision-making to enhance sales strategies and company competitiveness.